2005
DOI: 10.4049/jimmunol.174.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Specific Intercellular Transfer of MHC Class II to CD4+ T Cells Directly from the Immunological Synapse upon Cellular Dissociation

Abstract: The transfer of membrane proteins from APC to T cells was initially described in the 1970s, and subsequent work has described two mechanisms of transfer: APC-derived exosomes and direct transfer of small packets, while cells remain conjugated. Using fibroblast APC expressing a GFP-tagged I-Ek molecule with covalently attached antigenic peptide, we observed a third mechanism in live cell imaging: T cells spontaneously dissociating from APC often capture MHC:peptide complexes directly from the immunological syna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
106
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(115 citation statements)
references
References 54 publications
(73 reference statements)
5
106
0
Order By: Relevance
“…Although the existence of distinct thresholds for cytotoxicity and cytokine production has been reported previously [5], we now find that these thresholds correlate with differences in the amounts of antigen captured via trogocytosis, reinforcing the possibility that the antigen captured could play a role in the process of T cell activation, as shown recently by others in CD4 T cells: acquired peptide-MHC class II complexes colocalised with the TCR, p56 lck and phospho-tyrosines in CD4 + T cells, suggesting that the acquired peptide-MHC complexes could still engage the TCR and promotes signalling [37].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although the existence of distinct thresholds for cytotoxicity and cytokine production has been reported previously [5], we now find that these thresholds correlate with differences in the amounts of antigen captured via trogocytosis, reinforcing the possibility that the antigen captured could play a role in the process of T cell activation, as shown recently by others in CD4 T cells: acquired peptide-MHC class II complexes colocalised with the TCR, p56 lck and phospho-tyrosines in CD4 + T cells, suggesting that the acquired peptide-MHC complexes could still engage the TCR and promotes signalling [37].…”
Section: Discussionsupporting
confidence: 87%
“…As far as T cells are concerned, the capture of pepMHC complexes has been proposed to control CTL responses negatively by means of fratricide [18,32] (explaining, at least in part, the phenomenon of CTL exhaustion reported to occur at high antigen loads [33][34][35]), tolerance induction [36] or immunoregulation [22]. On the other hand, once captured, pepMHC complexes have been found to be associated to areas of intracellular signalling, suggesting a role for acquired pepMHC complexes in sustained signalling [37].…”
Section: Introductionmentioning
confidence: 99%
“…Using fibroblasts expressing a GFP-tagged I-E k molecule with covalently attached antigenic peptide, Wetzel et al demonstrated a third mechanism, the cellular dissociation (58). With the help of live cell imaging, they showed that T cells, while spontaneously dissociating from APCs often capture MHC-peptide complexes directly from the immunological synapse.…”
Section: Dissociation-associated Pathwaymentioning
confidence: 99%
“…Thus, Wetzel and colleagues implicated the activation of T cells to spontaneous association and dissociation from MCC:GFP cells, as T cells formed a mature IS, expressed high levels of CD69, and displayed significant TCR-down-regulation. Removal of specific MHC-peptide ligands from APCs would limit their availability for other T cells, which may be an important event in controlling an immune response (58). Such Ag stripping from dendritic cells is seen in vivo, suggesting that stripping would prevent lower affinity T cells to access Ag, thereby generating a higher affinity T cell response (61).…”
Section: Dissociation-associated Pathwaymentioning
confidence: 99%
“…20,21 Surface molecule transfer has been predominantly reported for the transfer of DC surface molecules to T cells in a unidirectional manner. 22,23 As a result, T cells with acquired DC molecules have been shown to be either immunogenic 12,24 or tolerogenic 25,26 in their effect on immune responses. In addition, T cells with uptake of DC-released EXO have been used as T-cell vaccines for stimulation of antitumor immunity.…”
Section: Discussionmentioning
confidence: 99%